(untitled) (Singaporean Journal of Business Economics and Management, 2026)
This study conducts a systematic literature review of 30 academic articles published between 2014 and 2024 to analyze the role of sustainability auditing in providing assurance over Environmental, Social, and Governance (ESG) disclosures. Using the Systematic Literature Review (SLR) approach guided by the PRISMA framework, the study identifies four main factors influencing the quality of sustainability assurance: the characteristics of assurance providers, the level of assurance (reasonable vs. limited), assurance standards and frameworks (ISAE 3000 vs. AA1000AS), and auditor independence. The findings indicate that sustainability auditing has a significant positive impact on the credibility of ESG information, enhances the quality and balance of disclosures, and promotes improvements in corporate accountability through the formalization of data management systems and the strengthening of stakeholder dialogue. However, sustainability auditing practices face substantial challenges, including the complexity and subjectivity of ESG information, competency gaps among practitioners, the absence of mandatory requirements in many jurisdictions, and suboptimal cost–benefit considerations. Data from KPMG show that although 99% of G250 companies reported sustainability information in 2024, only 71% obtained external assurance, indicating significant room for improvement. This study concludes that sustainability auditing is a critical mechanism within the corporate accountability ecosystem; however, its effectiveness depends on the harmonization of standards, stronger regulatory frameworks, enhanced auditor competence, and companies’ genuine commitment to sustainability transparency.